Supporting tools for participatory mapping - Vu Hong Trang (International Rice Research Institute, 2022)
The presentation introduced the training participants on the supporting tools that can be used for developing Climate-Smart Mapping and Adaptation Planning (CS-MAP), such as: focus group discussion, key informant interview, listing climate-risks, and Pairwise priority ranking.